ADSORPTION STUDIES ON THE REMOVAL OF Fe (II) ION FROM AQUATIC ENVIRONMENT USING NANO POROUS CARBON - Sivakumar, R; Arivoli, S (IJRDO-Journal of Applied Science, 2017)
The present study is on adsorption of Fe(II) ions by Activated Syringodium Isoetifolium Leaves Nano Carbon. It uses batch adsorption techniques. The influence of contact time, initial concentration, dosage of adsorbent and effect of solution pH were investigated. The equilibrium adsorption data were correlated with Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Hurkins-Jura, Halsay, Radlich-Peterson, Jovanovic and BET isotherm models. The isotherm studies of RL values showed that the adsorption process was favorable. Thermodynamic parameters such as ∆H0 , ∆S 0 and ∆G0 were evaluated. The data indicate that, the adsorption was spontaneous and is an endothermic nature. Adsorption kinetics was tested with pseudo- secondorder, Elovich model and intra – particle diffusion models. Kinetic studies indicate an adsorption pseudo-second-order reaction. This study shows that intra-particles played a major role in the adsorption of Fe(II) ions mechanism. The Activated Syringodium Isoetifolium Leaves Nano Carbon has high adsorption capacity and adsorption rate for the removal of Fe(II) ions from aqueous solution